Systemic administration of transforming growth factor-beta 2 prevents the impaired bone formation and osteopenia induced by unloading in rats. - Machwate, M; Zerath, E; Holy, X; Hott, M; Godet, D; Lomri, A; Marie, P J (The Journal of Clinical Investigation, 1995)
We investigated the effect of recombinant human transforming growth factor beta 2 (rhTGF-beta 2) administration on trabecular bone loss induced by unloading in rats. Hind limb suspension for 14 d inhibited bone formation and induced osteopenia as shown by decreased bone volume, calcium and protein contents in long bone metaphysis. Systemic infusion of rhTFG-beta 2 (2 micrograms/kg per day) maintained normal bone formation rate, and prevented the decrease in bone volume, bone mineral content, trabecular thickness and number induced by unloading. In vitro analysis of tibial marrow stromal cells showed that rhTGF-beta 2 infusion in unloaded rats increased the proliferation of osteoblast precursor cells, but did not affect alkaline phosphatase activity or osteocalcin production. Northern blot analysis of RNA extracted from the femoral metaphysis showed that rhTGF-beta 2 infusion in unloaded rats increased steady-state levels of type I collagen mRNA but not alkaline phosphatase mRNA levels. rhTGF-beta 2 infusion at the dose used had no effect on metaphyseal bone volume and formation, osteoblast proliferation or collagen expression in control rats. The results show that systemic administration of rhTGF-beta 2 enhances osteoblast precursor cell proliferation and type I collagen expression by osteoblasts, and prevents the impaired bone formation and osteopenia induced by unloading. Images